Education in the oral tradition of the African matrix in Brazil: Ancestry, resistance and human constitution - Daniela Barros; Saulo Pequeno; Patrícia Lima Martins Pederiva (Arizona State University, 2018)
This article discusses the educative processes in the oral tradition of the African matrix in Brazil, understanding the transmission of traditional knowledges as a process of human constitution. This oral tradition, built upon ancestry, brings in its essence the resistance to the colonization and keeps resisting, transmitting orally the traditional knowledges, memory and history. The educative process in the oral tradition of African matrix constitute in their holders a combative posture to the oppressions of the modern/colonial world-system. The article is result of an ethnography in groups and communities of oral tradition in two cities in the state of Bahia, Brazil: the Casa de Oxumarê, in the city of Salvador, and in the traditional cultures of Samba de Roda, Chegança and Renda de Bilros in the city of Saubara. It investigates how the educative processes occur through orality and how they contribute to the human constitution of their holders. It concludes that the ancestry consciousness is the anti-colonial educative element, in which the traditional groups and communities of African matrix in Brazil keep reaffirming to the world their ways of educating, resisting and re-existing.